Comparison of Renal Function and Other Predictors in Lacto–Ovo Vegetarians and Omnivores With Chronic Kidney Disease. (18th August 2018) - Chang, Chou-Yueh; Chang, Horng-Rong; Lin, Hsing-Chun; Chang, Han-Hsin
ABSTRACT: Objective Vegetarian diets have been shown to increase the risk of certain nutritional deficiencies, such as iron. As a number of patients with chronic kidney disease (CKD) in Taiwan are lacto–ovo vegetarians, the aim of this study was to investigate the effects of different proportions and sources of protein in lacto–ovo vegetarian and omnivorous diets, as well as the influence of adequate dietary protein intake, on renal function and nutritional status of Taiwanese patients with stage 3 to stage 5 CKD. Methods This is a cross-sectional study. In total, 100 outpatients with stage 3 to stage 5 CKD were enrolled in this study, including 40 lacto–ovo vegetarians and 60 omnivores. Subjects were divided into the lacto–ovo vegetarian group and omnivorous group based on dietary protein patterns. The indicators of renal function included estimated glomerular filtration rate (eGFR), creatinine, and blood urea nitrogen (BUN). Albumin, hemoglobin (Hb), and red blood cell count (RBC) measurements served as nutritional indicators. The levels of dietary energy and protein, as well as protein sources (plant or animal), were also analyzed. Results The levels of serum phosphate and triglycerides were significantly lower in the lacto–ovo vegetarian group than in the omnivore group, suggesting that lacto–ovo vegetarian diets have both phosphate-lowering and lipid-lowering effects, which could reduce the development of hyperphosphatemia and dyslipidemia. However, since all groups consumed higher than the recommended amounts of protein diet intake, no significant differences were observed in other renal function indices between the two groups. Conclusion Although a larger cohort study is necessary, the findings of this study could help patients with CKD to make healthier food choices and be used to support future medical nutritional therapies.